Perceived Learning Strategies Employed by Preschoolers in Learning English - Zuraina Binti Ali (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
Learning strategies are plans that learners use to achieve their learning goals. The current study investigates the perceived uses of learning strategies among preschoolers, namely Basic rehearsal strategies, Complex rehearsal strategies, Basic elaboration strategies, Complex elaboration strategies, Basic organizational strategies, Complex organizational strategies, Comprehension monitoring strategies and Affective and motivational strategies among preschoolers in learning English. The study employed 23 preschool teachers as the samples having semi-structured interviews as the research instrument. Findings from the study showed that the learning strategies were implemented by the preschoolers in the course of their learning. Yet, the degree of the usages of the learning strategies varies from one to another. The study implied that deciding on learning games, teaching aids, and asking appropriate questions during lessons are essential to maximize the learning strategies among children in their early learning.